2022
DOI: 10.1186/s12903-022-02181-7
|View full text |Cite
|
Sign up to set email alerts
|

Where do you live? North versus Central-South differences in relation to Italian patients with oral lichen planus: a cross-sectional study from the SIPMO (Italian Society of Oral Pathology and Medicine)

Abstract: Background Oral lichen planus (OLP) is an immune-mediated inflammatory chronic disease of the oral mucosa, with different patterns of clinical manifestations which range from keratotic manifestations (K-OLP) to predominantly non-keratotic lesions (nK-OLP). The aim of the study was to analyze the differences in the clinical, psychological profile and symptoms between Italian patients of the North and Central-South with K-OLP and nK-OLP. Methods 270 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For paediatric lichen planus, possible associations with hepatitis B virus (HBV) or hepatitis B vaccination have been described ( 11 ). Moreover, genetic factors, lifestyle, and emotional stress might be contributing factors in OLP pathogenesis ( 12 , 13 ). In particular, in patients with paediatric lichen planus a higher incidence of positive family history for the disease is reported ( 14 ); on the other hand, genetic linkage studies reported an association between familial lichen planus and HLA B, HLA DR1 and DR10 ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…For paediatric lichen planus, possible associations with hepatitis B virus (HBV) or hepatitis B vaccination have been described ( 11 ). Moreover, genetic factors, lifestyle, and emotional stress might be contributing factors in OLP pathogenesis ( 12 , 13 ). In particular, in patients with paediatric lichen planus a higher incidence of positive family history for the disease is reported ( 14 ); on the other hand, genetic linkage studies reported an association between familial lichen planus and HLA B, HLA DR1 and DR10 ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent systematic review, the oral mucosa is involved in 22% of pediatric patients, compared to 30%–70% of adult patients 2 . The low incidence of OLPc seems to be related to factors such as low incidence of systemic and autoimmune diseases, low levels of stress (considered a exacerbation trigger factor in adults), less usage of amalgam and orthodontic materials, which were recognized precipitating factors 3,4 in adults, as well as no tobacco consumption, which is a known risk factor for oral LP, 5 and fewer symptoms, leading to a number of undiagnosed cases 6–9 . This study reports clinical findings, treatments, and outcomes of 13 Italian patients with OLPc diagnosed between 2001 and 2021.…”
Section: Introductionmentioning
confidence: 99%
“…2 The low incidence of OLPc seems to be related to factors such as low incidence of systemic and autoimmune diseases, low levels of stress (considered a exacerbation trigger factor in adults), less usage of amalgam and orthodontic materials, which were recognized precipitating factors 3,4 in adults, as well as no tobacco consumption, which is a known risk factor for oral LP, 5 and fewer symptoms, leading to a number of undiagnosed cases. [6][7][8][9] This study reports clinical…”
mentioning
confidence: 99%
“…Among the main oral cancers, we have oral squamous cell carcinoma (OSCC), which represents about 90% of total cases [ 28 ]; histologically, it consists of a multi-layered epithelium consisting of squamous cells with the presence of cellular and nuclear atypia [ 29 ]; clinically, it can manifest itself as an ulcer (erythroplakia) [ 30 ], or a white plaque (leukoplakia) [ 31 , 32 ] sometimes ulcerated with poorly defined margins, the localization of which can affect the entire epithelium of the oral cavity [ 31 ]. The annual incidence in the world is 350,000 new cases diagnosed, with a higher incidence in the population over 50 years of age [ 33 ].…”
Section: Introductionmentioning
confidence: 99%